A helical membrane-binding domain targets the Toxoplasma ROP2-family to the parasitophorous vacuole - Reese, Michael L. (2009)
During invasion, the obligate intracellular pathogen, Toxoplasma gondii, secretes into its host cell a variety of effector molecules, several of which have been implicated in strain-specific variation in disease. The largest family of these effectors, defined by the canonical member ROP2, quickly associates with the nascent parasitophorous vacuole membrane (PVM) after secretion. Here we demonstrate that the NH(2)-terminal domain of the ROP2-family contains a series of amphipathic helices that are necessary and sufficient for membrane association. While each of the amphipathic helices is individually competent to bind cellular membranes, together they act to bind the PVM preferentially, possibly through sensing its strong negative curvature. This previously uncharacterized helical domain is an evolutionarily robust and energetically efficient design for membrane association.